MODERN APPROACHES TO UNDERSTANDING BIG DATA IN GLOBAL HEALTHCARE SYSTEM - Imamalieva Diyora Imamali kizi (Scholar Express Journals, 2023)
The topic of the article on the main legal aspects of big data in healthcare is relevant and in demand in modern society. The development of technologies, such as Big Data and artificial intelligence, is making a significant impact on the healthcare industry, providing new opportunities to improve diagnosis, treatment and the provision of medical services in general. However, with these technologies there are difficulties in legal regulation related to data protection, confidentiality, ethical issues and other aspects. Therefore, research in the field of legal regulation of big data and artificial intelligence in healthcare is relevant to ensure the effective and safe implementation of these technologies in medical practice.
Keywords: Big Data; biomedicine; healthcare system